Cultural Conflict in “Alif Lam Mim” and “My Name is Khan” Movies - Sartika, Endang; Laelatul Hida, Sukma; Amalia Putri, Dewi; Alia Anzani, Rahma; Maesaroh, Siti (International Proceedings of Nusantara Raya, 2022)
This study aims to analyze the social conflict in a film. The objects of this research are "Alif Lam Mim" and "My Name Is Khan" movies. Data were collected by watching the movies, identifying cultural conflicts, and analyzing cultural conflicts in it This research is a qualitative descriptive study which is used to determine the cultural conflicts occurred in these two movies. In "Alif Lam Mim" movie, it shows that cultural conflicts occurred between Muslims and the government where Islam is considered weak, and is easy to be dropped by terrorist Islamic stereotypes for profit. Then, in "My Name Is Khan" movie, it shows that cultural conflict occurred between Rizwan (a Muslim) with American society, where all Muslims are considered as terrorists. The reason for choosing the research in these two movies is because these two movies raised the same topic, which is the negative stereotypes of society on Islam and have same title, which is using Islamic name of characters. Both of these movies have the view that Islam is a violent religion, treason and full of greed. The conclusion that can be drawn from this research is that intercultural understanding is needed to maintain peace between nations and countries.